2018
DOI: 10.1139/cgj-2017-0446
|View full text |Cite
|
Sign up to set email alerts
|

Use of tire-derived aggregate in tunnel cut-and-cover

Abstract: Abstract.A case-history is reported in which tire derived aggregate (TDA) was successfully applied to reduce the weight of fill upon a cut-and-cover railway tunnel. Subsequent 3D numerical analyses are used to explore the effect of different assumptions about the constitutive model of the TDA material. Alternative dispositions of TDA around the tunnel section are also examined. Reductions of up to 60% in lining bending moment may be achieved. For the case analyzed the elastic description of the TDA has little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Since these models seem more suitable to simulate the behaviour of these materials, this paper studied the influence of the constitutive model of the TDA material on the level of vibration transmission. Other authors, such as Medina et al [ 33 ] have applied these constitutive models in cases of lightweight tunnel backfills, in which this material was used to reduce strains and stresses in the tunnel lining.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since these models seem more suitable to simulate the behaviour of these materials, this paper studied the influence of the constitutive model of the TDA material on the level of vibration transmission. Other authors, such as Medina et al [ 33 ] have applied these constitutive models in cases of lightweight tunnel backfills, in which this material was used to reduce strains and stresses in the tunnel lining.…”
Section: Resultsmentioning
confidence: 99%
“…For the nonlinear isotropic model, the following stress–strain relationship was used: where ε is the axial strain (%), σ the axial stress (kPa), and a and b are parameters that need to be adjusted. In this case, the values deduced by Medina et al [ 33 ] were used and are shown in Table 5 . In the case of the linear anisotropic model, the adopted values were also taken from [ 33 ] and are also shown in Table 5 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations